Umbilical cord blood concentration of connecting peptide (C-peptide) and pregnancy outcomes - Atrin Niknam; Fahimeh Ramezani Tehrani; Samira Behboudi-Gandevani; Maryam Rahmati; Mehdi Hedayati; Mehrandokht Abedini; Faegheh Firouzi; Farahnaz Torkestani; Mehdi Zokaee; Fereidoun Azizi (BMC, 2022)
Abstract Background C-peptide offers potential as a marker to indicate childhood metabolic outcomes. Measuring C-peptide concentration might have better future utility in the risk stratification of neonates born to overweight or diabetic mothers. Prior research has tried to bring this matter into the light; however, the clinical significance of these associations is still far from reach. Here we sought to investigate the associations between fetomaternal metabolic variables and umbilical cord blood C-peptide concentration. Methods For the present study, 858 pregnant women were randomly selected from among a sub-group of 35,430 Iranian pregnant women who participated in a randomized community non-inferiority trial of gestational diabetes mellitus (GDM) screening. Their umbilical cord (UC) blood C-peptide concentrations were measured, and the pregnancy variables of macrosomia/large for gestational age (LGA) and primary cesarean section (CS) delivery were assessed. The variation of C-peptide concentrations among GDM and macrosomia status was plotted. Due to the skewed distribution of C-peptide concentration in the sample, median regression analysis was used to identify potential factors related to UC C-peptide concentration. Results In the univariate model, positive GDM status was associated with a 0.3 (95% CI: 0.06 − 0.54, p = 0.01) increase in the median coefficient of UC blood C-peptide concentration. Moreover, one unit (kg) increase in the birth weight was associated with a 0.25 (95% CI: 0.03 − 0.47, p = 0.03) increase in the median coefficient of UC blood C-peptide concentration. In the multivariate model, after adjusting for maternal age, maternal BMI, and macrosomia status, the positive status of GDM and macrosomia were significantly associated with an increase in the median coefficient of UC blood C-peptide concentration (Coef.= 0.27, 95% CI: 0.13 − 0.42, p < 0.001; and Coef.= 0.34, 95% CI: 0.06 − 0.63, p = 0.02, respectively). Conclusion UC blood concentration of C-peptide is significantly associated with the incidence of maternal GDM and neonatal macrosomia. Using stratification for maternal BMI and gestational weight gain (GWG) and investigating molecular markers like Leptin and IGF-1 in the future might lay the ground to better understand the link between metabolic disturbances of pregnancy and UC blood C-peptide concentration.